Can Housing and Accessibility Information Influence Residential Location Choice and Travel Behavior? An Experimental Study. (June 2014) - Rodriguez, Daniel A; Rogers, Jennifer
Although information has been used as a strategy to influence short-term travel behavior, there is a paucity of research on whether information can result in long-term behavioral changes. To examine the impact of providing information on location choices and travel behaviors we used an experimental design with a sample of incoming students at two area universities. Information was administered to individuals in the experimental group before they selected a residential location in the area. With a survey, we collected information on residential locations and travel behaviors from all participants six months after the intervention. Students in the intervention group from one university traveled between 50% and 68% fewer km/day by automobile, located closer to the university, and located in areas with more transit stops than students in the control group. Information appears to be a promising strategy for influencing location decisions and prompting travel behavior change.